Integrating Prospective Scenarios in Life Cycle Engineering: Case Study of Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Energies)
Lightweight design is a common approach to reduce energy demand in the use stage of vehicles. The production of lightweight materials is usually associated with an increase in energy demand, so the environmental impacts of lightweight structures need to be assessed holistically using a life cycle assessment. To estimate the life cycle environmental impacts of a product in its developmental stage, for example, by life cycle engineering, future changes in relevant influencing factors must be considered. Prospective life cycle assessment provides methods for integrating future scenarios into life cycle assessment studies. However, approaches for integrating prospective life cycle assessment into product development are limited. The objective of this work is to provide the methodological foundation for integrating future scenarios of relevant influencing factors in the development of lightweight structures. The applicability of the novel methodology is demonstrated by a case study of a structural component in a steel, aluminium, and hybrid design. The results show that appropriate decarbonisation measures can reduce the life cycle greenhouse gas emissions by up to 95 percent until 2050. We also found that shifts in the environmentally optimal design are possible in future scenarios. Therefore, the methodology and data provided contribute to improved decision-making in product development.
Keywords: Life Cycle Engineering; Life Cycle Assessment; Lightweight Design; Prospective LCA; Future-oriented LCA; Energy System; Material production; Sustainable production

Digitalität, Mediatisierung und Bildung - Megatrends aus medienpädagogischer Perspektive - Herzig, Bardo (Bildung und Digitalität. Analysen - Diskurse - Perspektiven)

Modellbildung und Modellnutzung in der Allgemeinen Didaktik - Herzig, Bardo (Pädagogische Rundschau. Sackgasse oder Meilenstein? Zur Sinnhaftigkeit von Modellbildungen in der Erziehungswissenschaft)

Kinderstärkende Pädagogik in der Grundschule im Kontext (post-)pandemischer Herausforderungen. Kennzeichen, Kritische Anfragen und Blinde Flecke. Vortrag an der Tagung: Was Resilienz stärkt. Chancen und Risiken eines immer populärer werdenden Konzepts. Pädagogische Hochschule Heidelberg. - Büker, Petra

KrafT: Bildungsdokumentation in der inklusiven Schule partizipativ gestalten. 9. Paderborner Grundschultag zum Thema: „Demokratie Lernen von Anfang an“. Online - Büker, Petra; Herding, Jana; Drexler, Leonie

Investigation of change in dispersive behaviour during adhesive curing in multi-layered structures - Zeipert, Henning; von Germeten, Christian; Friesen, Olga; Claes, Leander; Johannesmann, Sarah; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Bestimmung der Volumenviskosität mittels akustischer Absorptionsmessung - Claes, Leander (Fortschritte der Akustik - DAGA 2023)

Characterization of adhesion strength using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Professionalisierung für Digitale Bildung im Grundschulalter. Ergebnisse des Forschungsprojekts P³DiG
Durch Digitalisierung und Digitalität entstehen neue Fragestellungen für die formale und non-formale Bildung. Insbesondere die Professionalisierung von Lehrkräften und Fachpersonal steht durch die Dynamik der technologischen und kulturellen Entwicklungen vor weitreichenden Herausforderungen. Der vorliegende Band beschäftigt sich mit der Frage der Professionalisierung von Grundschullehrkräften und pädagogischen Fachkräften für eine Digitale Bildung im Grundschulalter und ist auf der Grundlage des BMBF-Projekts Primat des Pädagogischen in der Digitalen Grundbildung – Grundsatzfragen und Gelingensbedingungen in der Professionalisierung von pädagogischen Akteur:innen für Kinder im Grundschulalter, P3DiG, entstanden. Im ersten Teil des Sammelbandes werden Grundlagen der Professionalisierung für eine Digitale Grundbildung dargelegt. Im zweiten Teil werden die Ergebnisse des Projekts präsentiert. Dabei werden sowohl Professionalisierungsmodelle für eine Digitale Grundbildung als auch die Ergebnisse der im Projekt durchgeführten empirischen Untersuchungen zur Digitalen Grundbildung im Grundschulalter vorgestellt. Der Band kann damit als Grundlage für die Ausarbeitung von Professionalisierungskonzepten in Hochschulen, Seminaren und Weiterbildungseinrichtungen dienen und liefert Impulse für die weitere wissenschaftliche Auseinandersetzung.

Modelling electron exchange and correlation for catalyst electronic structure simulations - Badalov, Sabuhi

Circularly polarized electroluminescence from a single-crystal organic microcavity light-emitting diode based on photonic spin-orbit interactions - Jia, Jichao; Cao, Xue; Ma, Xuekai; De, Jianbo; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Automatisierung der Auswertung rheologischer Messungen (Studienarbeit) - Gunasagran, Sharin Kumar; Neukötter, Moritz

Examining the Measurement Invariance and Convergent Validity of the SSIS-SELb-Student in Austria and Germany. 44th Annual Conference of the International School Psychology Association (ISPA) 2023. - Anthony, Christopher J.; Yost, M; Howe, A; Schwab, Susanne; Hassani, Sepideh; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Striewe, Marius; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Analysis of temperature effect on strength and microstructure in friction induced recycling process (FIRP) - Borgert, Thomas; Homberg, Werner (Materials Research Proceedings)
Abstract. In order to reduce global energy consumption in production and industry along with the associated CO2 emissions, existing resources must be used more efficiently. This includes the energy-efficient and comprehensive recycling of a wide range of metals. Especially for the production of aluminium, there is a large potential for saving energy using efficient recycling processes. With regard to the recycling of aluminium studies have shown that solid-state recycling processes are significantly more efficient considering the used energy and resources compared to the conventional, smelting-metallurgical recycling process. In this paper, the direct and energy-efficient friction-induced recycling process (FIRP) based on the conform process is further described and analysed in terms of the temperature-property relationships. For this purpose, the influence of the processing temperature on the microstructure and properties of the recycled semi-finished products is investigated using the toll system that enables an ECAP forming. Specific sections of the (in theory) infinite, recycled semi-finished product are taken and analysed at different process temperatures of the solid state recycling process. Based on these sections, the properties in terms of mechanical hardness, strength, ductility and grain size are analysed and a degressive relationship between process temperature and mechanical hardness up to a temperature of 270 °C can be shown. Applying the Hall-Petch relationship, it is analysed whether there is a correlation between the strength and the microstructure in the form of the grain size.
Keywords: Recycling; Aluminium; Friction-Induced; Energy Efficiency

Untersuchung überlagerter Effekte von Druckverlust und Totvolumen durch Rekuperation am isobaren Expansionsmotor - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny Y. (Chemie Ingenieur Technik)
Die Wirtschaftlichkeit von Wärmemotoren wird maßgeblich durch die Rückführung von Wärme in Rekuperatoren beeinflusst. Beim isobaren Expansionsmotor vom Bush-Typ, einem Wärmemotor, welcher bereits mit Wärmequellen ab 60°C betrieben werden kann, steigt der thermische Wirkungsgrad durch den Einsatz von Rekuperatoren signifikant. Gleichzeitig wirken sich das Fluidvolumen des Wärmeübertragers sowie der beim Betrieb auftretende Druckverlust negativ auf den thermischen Wirkungsrad aus. In dieser Arbeit wird der Zusammenhang von Totvolumen, Druckverlust und Wärmerückgewinnung untersucht und Empfehlungen für den Betrieb von Rekuperatoren am isobaren Expansionsmotor gegeben.
Keywords: Isobarer Expansionsmotor; Dynamische Wärmeübertragungsmodellierung; Phasenwechsel; dichte Arbeitsmedien

Investigation of the leak tightness of structural adhesive joints for use in battery housings considering mechanical and corrosive loads - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie)
Keywords: General Medicine